Genetics of arginine and proline biosynthesis in Neisseria gonorrhoeae. - Picard, François J. (University of Ottawa (Canada), 1991)
The carAB operon from E. coli hybridized with the gonococcal clones carrying carA or carB genes under conditions of high stringency (i.e. detecting approximately 80% or greater similarity) suggesting that the nucleotide sequence of the carbamoylphosphate synthetase genes is very similar in these two organisms. Under these conditions for hybridization, the gonococcal clones carrying argB or argF genes did not hybridize with plasmids containing the corresponding E. coli gene. Hybridizations performed under conditions of lower stringency indicate that the nucleotide sequence of the argB gene is less conserved than that of argF in E. coli and N. gonorrhoeae. Co-complementation experiments established gene linkage only between carA and carB and between proA and proB gonococcal genes. Clones complementing a gene defect in argE were also able to complement an argA mutation. This suggests that the enzyme ornithine acetyltransferase from N. gonorrhoeae (encoded by argJ) may be able to complement both argA and argE mutations in E. coli. The prevalence of specific arginine biosynthesis gene defects was studied for 319 arginine-requiring clinical isolates of Neisseria gonorrhoeae by using the ability of the strains to utilize intermediates of arginine biosynthesis. Nearly 99% of the strains were defective either in the conversion of acetylornithine to ornithine (174 strains) or in the conversion of ornithine to citrulline (141 strains). Based on a nutritional requirement for carbamoyl phosphate, only 11% of the uracil-requiring strains defective in the carbamylation of ornithine to yield citrulline were apparently defective in carAB. Three argininosuccinate-requiring strains (i.e. probably defective in argG) of auxotype PAU were identified. A high polymorphism was observed in hybridization patterns of restricted genomic DNA from N. gonorrhoeae strains having the same auxotype and serotype with a gonococcal CPSase gene-specific probe suggesting that this probe may provide a useful epidemiological marker for N. gonorrhoeae. Some of the arginine auxotrophs of N. gonorrhoeae defective in carAB, argJ, argF or argG were complemented by genetic transformation with DNA from recombinant bacteriophages carrying characterized gonococcal arginine biosynthesis genes. Gene defects in proA (5 strains) and in proB (6 strains) were identified by gonococcal transformation assays with recombinant bacteriophages or plasmids carrying proline biosynthesis genes from N. gonorrhoeae. None of the eleven proline-requiring strains tested appears to be defective in proC. Polymerase chain reaction (PCR) amplifications using oligonucleotides specific to conserved areas of the E. coli carAB operon yielded amplified copies of various portions of the N. gonorrhoeae CPSase genes. Amplifications using primers specific to the duplicated region of the E. coli carB gene suggest that the gonococcal carB gene contains a similar duplication. (Abstract shortened by UMI.)
Keywords: Biology, Genetics.